Microglia Don’t Treat All Neurons the Same: The Importance of Neuronal Subtype in Microglia-Neuron Interactions in the Developing Hypothalamus - Ngozi, Zuri; Bolton, Jessica L. (Frontiers in Cellular Neuroscience, 2022)
Microglia are now well-known as integral regulators of brain development, phagocytosing whole neurons, and pruning weak or excess synapses in order to sculpt and refine immature circuits. However, the importance of neuronal subtype in guiding microglial activity has not received much attention until recently. This perspective will delineate what is known about this topic so far, starting with the developing brain as a whole and then focusing on the developing hypothalamus in particular. There is emerging evidence that subpopulations of microglia treat excitatory and inhibitory neurons differently, and our recent work has shown that even the type of neuropeptide produced by the nearby neurons is important. For example, microglia abutting corticotropin-releasing hormone (CRH)-expressing neurons in the paraventricular nucleus of the hypothalamus (PVN) engulf fewer excitatory synapses than do microglia on the borders of the PVN that are not contacting CRH+ neurons. Potential future directions and technical considerations will be discussed in an effort to catalyze this emerging and exciting area of research. Applications of this research may hold promise in creating more specific therapies that target unique subtypes of microglia-neuron interactions in the atypically developing brain.